Health-related quality of life after anterior cruciate ligament reconstruction: a systematic review - Filbay, S; Ackerman, I; Russell, T; al., E (SAGE Publications, 2014)
BACKGROUND: Anterior cruciate ligament reconstructions (ACLRs) are frequently performed on young, active patients and can result in persistent knee symptoms and activity limitations that may affect health-related quality of life (HRQoL). To date, there has been no systematic review of HRQoL outcomes after ACLR. PURPOSE: The objectives of this study were to report HRQoL ≥5 years after ACLR, compare HRQoL outcomes with available population norms, and describe factors that may affect HRQoL in this population. STUDY DESIGN: Systematic review. METHODS: All studies reporting HRQoL ≥5 years after ACLR with hamstring or patellar tendon autografts were eligible for review. Common HRQoL outcomes were pooled using a random-effects meta-analysis and compared with published population norms. The Spearman rank correlation coefficient (ρ) was used to identify variables associated with HRQoL outcomes. Where insufficient data were available, outcomes were reported descriptively. RESULTS: Fourteen studies were eligible for review, and HRQoL was reported for 2493 patients at a mean of 9 years (range, 5-16 years) after ACLR. Pooling of knee-related quality of life outcomes (Knee injury and Osteoarthritis Outcome Score [KOOS]-QOL) found impairments after ACLR when compared with population norms. In comparison, studies using the Short Form-36 (SF-36) reported similar or better HRQoL compared with normative data. The KOOS-QOL subscores correlated strongly with KOOS-sport/recreation (ρ = .70, P = .04) and KOOS-pain (ρ = .85, P = .003) subscores. Severe radiographic osteoarthritis, meniscal injuries sustained after surgery, and revision ACLR were associated with poorer HRQoL outcomes at a minimum 5-year follow-up. The negative influence of concomitant meniscal surgery on HRQoL became apparent more than 10 years after ACLR. CONCLUSION: This review found that patients assessed using a knee-specific measure (KOOS-QOL) were more likely to report poorer HRQoL values, compared with population norms, than those assessed using a generic HRQoL measure (SF-36). Revision surgeries, meniscal injuries, and severe radiographic osteoarthritis were associated with poorer HRQoL outcomes after ACLR. However, these relationships should be interpreted with caution, as they were only investigated in a small number of studies. CLINICAL RELEVANCE: These results can be used by clinicians to educate patients about potential long-term outcomes after ACLR and to develop strategies for optimizing postoperative HRQoL.